THE EFFECT OF TAXPAYER AWARENESS, TAX SANCTIONS, QUALITY OF FISCAL, AND APPLICATION OF THE E-FILING SYSTEM ON COMPLIANCE OF INDIVIDUAL NON-ENTREPRENEUR TAXPAYERS REGISTERED AT KRAMAT JATI TAX SERVICE OFFICE - Oktaviani, Bernadeta; Triyani, Yustina (AIBPM Publisher, 2023)
Taxes are the largest source of state revenue included in the APBN among other revenues. All taxpayers are required to pay and report taxes owed, but the annual SPT reporting reported by taxpayers from year to year is still not optimal, of course this is an obstacle to increasing taxpayer compliance. The research was conducted to determine the effect of taxpayer awareness, tax sanctions, quality of tax services, and the application of the e-filing system on the compliance of individual non-entrepreneur taxpayers registered at KPP Pratama Kramat Jati. The data obtained in this study amounted to 100 questionnaires distributed using a non-probability sampling technique with a purposive sampling method. The analysis technique uses multiple regression with the SPSS program. The results of the research data test have a Sig value on the t-test for the taxpayer awareness variable 0.000, tax sanctions 0.350, the quality of tax services 0.002, and the application of the e-filing system 0.194. The research conclusion obtained is that there is sufficient evidence that awareness of taxpayers and tax authorities have a positive effect on taxpayer compliance. Meanwhile, tax sanctions and the implementation of e-filing don’t have enough evidence to have a positive impact on taxpayer compliance.